Peranan Etika Administrasi Bagi Aparatur Pajak (Fiskus) dalam Meningkatkan Kepatuhan Perpajakan - Rio Fernando Alexander (Syntax Corporation Indonesia, 2024)
This research aims to evaluate the role of administrative ethics in enhancing tax compliance levels, particularly among tax officials and taxpayers in Indonesia. Adopting a qualitative approach through a literature review, this study discusses the concept of administrative ethics, tax compliance, and the impact of ethical administrative practices on public trust in the tax system. The results indicate that strong ethical administrative practices can create a climate of trust among taxpayers, stimulate compliance, and reduce non-compliance practices in the tax environment. The practical implications of this research include the pivotal role of administrative ethics in boosting tax revenue and building a foundation of trust within the tax system.